P16 Cancer survivors' experience with telehealth: a systematic review and thematic synthesis. (20th March 2019) - Cox, Anna; Lucas, Grace; Marcu, Afrodita; Grosvenor, Wendy; Mold, Freda; Maguire, Roma; Piano, Marianne; Ream, Emma
Abstract : Background: There is a drive to transfer the care of cancer survivors to the community and encourage them to play an active role in their own care. Telehealth is an important contributor to this evolving model of care but we are lacking an integrative perspective and in-depth understanding of how cancer survivors accept it, engage with it, and benefit from it. Objective: To systematically identify, appraise, and synthesize qualitative research evidence on the experiences of adult cancer survivors participating in telehealth interventions, to characterize the patient experience of telehealth interventions for this group. Methods: We searched PsycINFO, Medline, CINAHL, Embase, and Cochrane Central Register of Controlled Trials for studies published in English between 2006 and 2016 reporting qualitative data (including verbatim quotes) on adult cancer survivors' experience of participating in a telehealth care intervention (defined as remote communication or remote monitoring with a health care professional delivered by telephone, Internet, or hand-held or mobile technology). All papers underwent inductive analysis, involving comparison, re-examination, and grouping of codes to develop descriptive themes. Analytical themes were developed through an iterative process of reflection on, and interpretation of, the descriptive themes within and across studies. Results: Across 22 papers included in the review, three analytical themes emerged, each with three descriptive subthemes: (1) influence of telehealth on the disrupted lives of cancer survivors (convenience, independence, and burden); (2) personalized care across physical distance (time, space, and the human factor); and (3) remote reassurance—a safety net of health care professional connection (active connection, passive connection, and slipping through the net). Telehealth interventions represent a convenient approach to cancer care, which can potentially minimise treatment burden and disruption to cancer survivors' lives. Conclusions: Telehealth interventions can engender an experience of personalised care, while providing cancer survivors with independence and reassurance.